The Effect of Science e-Module to Enhance Students’ Critical Thinking Skills on the Object Classification Topic - Fahmi, Fahmi; Irhasyuarna, Yudha; Suryajaya, Suryajaya; Fajeriadi, Hery (Jurnal Pendidikan MIPA, 2025)
This study aims to develop innovative science teaching materials based on higher-order thinking skills (HOTS) to enhance students’ critical thinking skills on the topic of object classification. The research adopted the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 60 seventh-grade junior high school students as research subjects. Data were collected using expert validation sheets, student response questionnaires, and pretest-posttest instruments to assess students’ critical thinking skills. The results of expert validation indicated that the developed teaching materials were categorized as “highly valid,” with an average score of 92.5%, reflecting the quality in terms of content, presentation, language, and design. During implementation, students showed an increase in critical thinking performance. The average pretest score was 58.3, which improved to 78.7 in the posttest. A paired sample t-test analysis revealed a statistically significant difference between pretest and posttest scores (t = 8.624; p < 0.001), indicating the effectiveness of the developed material in improving critical thinking skills. Furthermore, student responses to the teaching materials were very positive, with an average score of 88.4%, suggesting that the materials were well-received and engaging. This study provides empirical support for integrating innovative HOTS-oriented learning materials into science instruction, particularly for foundational topics such as object classification. The findings contribute to the field of science education research and offer practical implications for the development of curriculum materials that foster critical thinking in junior high school students. These results can be used as a reference for educators and curriculum developers in designing effective, student-centered science learning tools.    Keywords: ADDIE model, critical thinking, instructional design, object classification, science teaching materials.